Uma proposta de capacitação na área da educação musical especial - Viana, Ana Célia de Lima (2015)
Special Music Education is the field of knowledge that covers music teaching and learning for students with special needs. This area has been growing timidly in Brazil, since on the one hand we have the inclusion of music in school programs after the enactment of Law 11.769/2008, on the other hand we have the inclusion of students with special needs in general classes at elementary school. In general, teachers claim not be prepared to work with these students with special needs, claiming lack of training as a major barrier. Thus, it is noted the interest of Brazilian researchers for identifying knowledge and skills required for music educators to work with such students and contribute to the improvement of training and music education in inclusive settings. International literature provides theoretical and practical information relevant to guide studies on training in the area of special musical education. This study aims at analyzing a set of knowledge and skills covered in a course for music educators to work with students with special needs in light of the contributions from such literature and the perceptions of teachers. The participants of the research were three musical educators. The course involved nine meetings in which it was tried to present and discuss with the participants the following set of knowledge related to music education for students with intellectual disability and hearing loss: importance of positive attitudes and beliefs about teaching and the learning process; the importance of obtaining information on different areas of the student s life, the use of appropriate tools to reach these information and how to assess the student s musical skills; characteristics of disabilities that may affect learning and the different types of recommended adjustments. The training involved reading texts about the subject, slideshow and videos, case study analysis of musical practices involving appropriate adjustments to illustrate the concepts, application of concepts and principles of exercises and examples of adjustments. Data for the description and analysis of the training has consisted of records from field diaries, materials and teaching resources and the review of the products of the activities undertaken by the participants. An initial questionnaire and a course assessment questionnaire were applied. The results indicate that the content covered in the training are in accordance with the literature recommendations about training for work in the special music education, and were considered relevant by the participants. The set of teaching materials and teaching and learning activities produced at this training provided information for use in further studies and to be available for in service and pre service music educators. It discusses the study limitations and possibilities for new investigations.